PROMOTION STRATEGY ANALYSIS OF MAKE UP ARTIST @MAUDY. MAKEUP USING INSTAGRAM SOCIAL MEDIA - Mariesa Dwi Ashari; Zahrotul Umami; Lisa Mardiana (Jurnal Ilmu Komunikasi, 2020)
The growing demand for makeup services, making more and more business players. Competition is also tight, it takes special tips from the Make Up Artist (MUA) in order to survive the middle of the competition. Instagram is growing rapidly as technology progresses. Using the upload feature through photos and videos, Instagram is used by many businessmen of goods or services to become a business land. For the businessman who sees the opportunity will not miss it, for example is Maudy Make Up Artist (MUA) who utilize Instagram as one of the promotional media for his business. This research aims to determine the analysis of the promotion strategy conducted by MUA @maudy. Makeup by using Instagram social media. The research methods used are qualitative research with descriptive research studies. Data is obtained through observation and interviews. The results of this study are in this study showing IMC a role in communicating the message that wants to be delivered @maudy. Makeup to audiences or Instagram users, especially to women as @maudy. Makeup targets. A promotional strategy conducted by Maudy make up artist that @maudy. Makeup in promotion on Instagram account @maudy. Makeup is by applying the promotional mix component i.e. advertising, direct marketing, interactive marketing, sales promotion, relationship and personal sales.